A Career Developmental Perspective on the Therapeutic Alliance: Implications for Counseling. Issue 2 (2nd June 2014) - Braunstein‐Bercovitz, Hedva; Cohen, Eitan; Geller, Shulamit; Benjamin, Benny A.
<x xml:space="preserve">Abstract</x> This review explores the role played by childhood emotional maltreatment (CEM) in selecting a career in the field of mental health and the potential positive and deleterious effects of these career‐choice motives on the therapeutic alliance. The reviewed findings support the assumption that CEM may serve as a precursor for career choice of professions in the mental health field. Implications are suggested for the counselor/therapist–client relationship, also known as the therapeutic alliance, as well as for career counseling.